Occupational hazards, injuries and illnesses associated with small scale gold mining: case of Ward 19, Zvishavane, Zimbabwe - Kusena, Winmore; Zhou, Tafadzwa (Midlands State University, 2015)
The paper sought to identify major occupational hazards, establish causes and nature of physical injuries and illnesses associated with small scale gold mines in Zvishavane. Three out of eleven identified mines from ward 19 were randomly selected for the study. Juxtaposed with observations, questionnaires were administered to all 34 mine employees in the respective mines to identify the types of hazards in the mines. Interviews were then conducted with three mine owners from each mine to establish the mines status quo with regards to injuries and illnesses. It was revealed that dust; heat, humidity, tools and equipment were the common hazards in all the mines. Substandard maintenance of tools and equipment as well as working under the influence of alcohol were identified as the major causes of injuries. These injuries included, among others, 20% lacerations, 20% cuts and 17 % crushes. The main reported illnesses were pneumoconiosis related due to the dusty environments the workers were always exposed to. The paper therefore advocates for more financial support from the mine owners towards employees’ safety in order to ensure a health and vibrant workforce for sustainability in production. Fundamental training programmes should be put in place to educate particularly the mine owners on the ultimate accrued benefits of safety on the employee and the nation at large.